Analysis of Factors Affecting the Intention to Donate Cash Waqf among Muslim Community at East Java Province - Hariyanto (Universitas Muhammadiyah Malang, 2022)
This study aims to determine the factors affecting the intention to donate cash waqf among Muslim community at East Java Province. This study uses quantitative methods with the data collected through an online survey questionnaire focuses on Muslims in East Java by approximately 110 responses were obtained. The data obtained were analyzed using the structural equation modeling-partial least square (SEM-PLS) analysis technique. The results found that trust and religiosity had a significant positive effect on cash waqf attitudes, while knowledge had no positive and insignificant effect. The results also show that attitudes, subjective norms, and PBC have a positive and significant effect on cash waqf intentions, while technology and promotion have no positive and insignificant effect on the intention of Muslims in East Java to donate cash waqf. Waqf institutions can increase promotion through websites and build a technology infrastructure that is even more attractive for the Muslims in East Java to interact and ultimately donate through cash waqf programs both offline and online. The results of this study contribute to enriching the discourse of cash waqf in Indonesia, especially in terms of the willingess to pay cash waqf in Indonesia.